Pengaruh Inovasi Pelayanan dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Pelayanan Ulam Sepat (Unit Layanan Adminduk Mobile Secara Cepat dan Tepat) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Nganjuk - Sinipat, Kartiko Nugroho Pangestu; Pradana, Galih Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Optimal population administration services serve as one of the key indicators in achieving governance that is responsive to the needs of the public. One of the efforts to realize this goal is through service innovation and the enhancement of public service quality. This study aims to analyze and evaluate the influence of service innovation and service quality on community satisfaction with the ULAM SEPAT service (Mobile Population Administration Service Unit for Fast and Accurate Delivery) at the Department of Population and Civil Registration of Nganjuk Regency. This research employs a quantitative approach through a case study on an outreach service program conducted at six service points within Nganjuk Regency. Data collection was carried out by distributing questionnaires to respondents who had utilized the ULAM SEPAT service, selected based on specific age ranges and criteria relevant to the service population. The independent variables in this study are service innovation and service quality, while the dependent variable is community satisfaction. The analytical method used in this study is Structural Equation Modeling (SEM) with second-order Confirmatory Factor Analysis (CFA), and data processing was conducted using Smart-PLS 3 software. The findings indicate that both service innovation and service quality have a significant influence on community satisfaction, with the coefficient of determination (R²) showing that 5 out of 12 indicators meet the “good” criteria and the remaining indicators meet the “moderate” criteria. This suggests a moderate to strong influence of the independent variables on community satisfaction. Furthermore, the f² test results reveal that service innovation exerts a stronger influence on community satisfaction compared to service quality, although both are categorized as having a strong effect. These findings highlight the importance of enhancing both aspects to provide population administrative services that are efficient, precise, and satisfactory..